The functioning in the borderland and the perception of cultural diversity In the declarations of polish and czech students - Anna Szafrańska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Due to the changing conditions of individual functioning of future teachers, the issue of preparing them for life in the culturally diversified environment is becoming increasingly important. The contemporary academic youth is in a particular situation, not only in regard to their participation in the quickly changing sociocultural world, but also in regard to their experiencing the phenomena which earlier have never been present on such a scale. What seems significant as well is that their identities and biographies are shaped by both macro-social and macro-economic tendencies. The reflection upon the young learning generation of Poles and Czechs is associated with an attempt to find answers to many questions. Among them, a lot of attention should be paid to those concerning their perception of the environment in which they function every day - the borderland. Learning different cultures in the borderland space takes place naturally and spontaneously, which is to a large extent enhanced by borderland trading and transfrontier activities. What results from these processes are many social attitudes to the unknown and undomesticated values carried by the Others. Therefore, my intention is to learn how young adults view the situation in the borderland, which is an effect of the functioning side by side of different nationality groups. Due to the requirements of this study, some descriptions and explanations have been prepared which refer to the issue of the respondents' perception of the situation in the borderland resulting from the functioning of different nationality groups.